Mirnodobne dejavnosti oboroženih sil kot vir ogrožanja okolja - Grčar, Silvo (Teorija in praksa, 2021)
Human existence and development depend on the environment. The armed forces is an organisation holding the capacity to cause environ- mental harm, even in peacetime. The phenomenology and etiology of the environmental crimes of the armed forces in green criminology have yet to be fully explored. The armed forces is a structural part of the political and economic organisation of the state, which regulates the functioning of the armed forces. The armed forces' peacetime activities are usually systemic and legal, even though they threaten the environment. On the global level, the armed forces is responsible for various forms of environmental crime in a generally open way. Society responds similarly to the armed forces' peacetime activities that threaten the environment and is the strongest factor in the social construction of environmental crime.
Keywords: armed forces; ekološka kriminaliteta; ekološka kriminologija; environmental crime; environmental harm; green criminology; military; oborožene sile; okoljska škoda; vojska